WAYS OF EFFECTIVE USE OF MODELING METHODOLOGY IN THE DEVELOPMENT OF SEMIOTICS IN MATHEMATICS IN YOUNG STUDENTS (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
In this article, the importance of semiotic aspects in teaching mathematics to young students, its applications, the necessary pedagogical conditions, the scientists and their views are described in detail, the branches, directions of semiotics and how we can use it in our daily life. passed.